Use of inhaled nitric oxide in pediatric cardiac intensive care unit - Erkut Öztürk; Sertaç Haydin; İbrahim Cansaran Tanıdır; İsa Özyılmaz; Yakup Ergül; Ersin Erek; Alper Güzeltaş; Ender Ödemiş; İhsan Bakır (KARE Publishing, 2016)
Objective: Experience with administration of inhaled nitric oxide (iNO) in pediatric cardiac intensive care unit was retrospectively reviewed. Methods: Data from 32 pediatric patients treated with iNO between 2011 and 2012 were collected. Patients were divided into 3 groups: Group I comprised postoperative patients, Group II comprised newborns with persistent pulmonary hypertension (PPH), and Group III comprised patients with primary pulmonary hypertension (PH) or Eisenmenger's syndrome. Age, sex, weight, primary diagnosis, arterial blood sample, pulmonary artery pressure (PAP), systemic arterial pressure (SAP), and oxygen saturation levels were analyzed. Results: Groups I, II, and III included 25, 3, and 4 patients, respectively. Median weight was 8 kg (range: 3-40 kg), and median age was 7 months (range: 2 days-10 years). On average, iNO treatment was initiated at the 12th hour after admission to the unit (range: 1-48 hours) and continued for a median duration of 24 hours (range: 12-168 hours). Systolic PAP was 40+-15 mmHg, mean SAP was 57+-18 mmHg, PAP/SAP ratio was 0.69, and oxygen saturation levels were 88% prior to iNO treatment. Following iNO treatment, PAP decreased to 24+-9 mmHg (p<0.05), PAP/SAP ratio decreased to 0.4 (p<0.05), SAP showed no change (60+-12 mmHg), and saturation levels increased to 98% (p<0.05). Seven patients died during follow-up (Group I, n=5; Group II, n=1; Group III, n=1). Conclusion: iNO seems to effectively reduce PAP, and can be used effectively and safely to prevent pulmonary hypertensive crises in pediatric cardiac intensive care units.